Only God can judge me : the many lives of Tupac Shakur - Pearlman, Jeff (Mariner Books, 2025)
"Scrutinized in life, mythologized in death, Tupac Shakur remains a subject of immense cultural significance and speculation nearly thirty years after his murder. Despite a multitude of books, documentaries, and even a feature film, much about Tupac's story remains shrouded and misunderstood. Like many icons who died tragically young, Tupac the man has long been obscured-his edges sanded down, his complexity numbed-by the competing agendas that surround his legacy. In ONLY GOD CAN JUDGE ME, accomplished biographer and cultural historian Jeff Pearlman tackles his most nuanced subject, telling the definitive story of Tupac Shakur in unprecedented depth. In this authoritative look at Tupac's life, Pearlman skillfully recreates West Coast hip hop in all its glory, going inside Death Row Records and on the sets of movies like Juice and Poetic Justice to offer the most clear-eyed rendering to date of the man who still casts a shadow over modern hip hop. But more than just a biography of a complicated figure, ONLY GOD CAN JUDGE ME also captures the time and place in which Tupac rose, a singular moment in music history when West Coast hip hop became a phenomenon and transformed popular music. Featuring nearly seven hundred original interviews and never-before-published details from every corner of Tupac's life, the result offers a truly singular portrait of one of modern pop culture's most towering figures. Guided by the voices of those who knew and lived life alongside him, ONLY GOD CAN JUDGE ME captures the layers of a man who, even thirty years after his death, remains as elusive as ever"-- Provided by publisher.